A rare case of urachal carcinoma with multiple lung metastasis that required differentiation from primary lung carcinoma. Issue 1 (7th December 2021) - Suzuki, Kentaro; Kai, Yoshiro; Matsuda, Masayuki; Horimoto, Kazuhide; Iwai, Kazunori; Takano, Masato; Yoshii, Masahito; Muro, Shigeo
Abstract: Urachal carcinoma is a rare malignancy of all bladder carcinomas. Metastatic lung tumours showing multiple nodules are rare without a local recurrence. We describe a case of multiple metastatic lung cancer from urachal carcinoma that required differentiation from primary lung cancer. Abstract : Urachal cancer, a rare malignancy, constitutes <1% of all bladder cancers. The prognosis of metastatic urachal cancer is extremely poor. Cases of distant metastasis without local recurrence alone are relatively rare. We describe a case of multiple metastatic lung cancer from urachal carcinoma that required differentiation from primary lung cancer.